1. ## please do it completely plzzz

(2x-2y-2z)^2
solve above!I mean expand using sonme sort of formula
plz dont joke me 4 such a questone I am a student of low level I mean low class oh junior class

2. Hi Peacewanters2007!

What exactly do you want to do with that? Do you need to expand it? Or is it part of an equation you need to solve?

3. $(a + b + c)^2 = (a + b + c)(a + b + c) =$ $a.a + a.b + a.c + b.a + b.b + b.c + c.a + c.b + c.c = a^2 + b^2 + c^2 + 2ab + 2ac + 2bc$

So, take $a=2x$, $b=-2y$, $c=-2z$,
$4x^2 + 4y^2 + 4z^2 - 8xy - 8xz + 8yz$

Or you could do this without using a formula,

$(2x - 2y - 2z)^2 = (2x - 2y - 2z)(2x - 2y - 2z) =$ $4x^2 - 4xy - 4xz -4xy + 4y^2 + 4yz - 4xz + 4yz + 4z^2 = 4x^2 + 4y^2 + 4z^2 - 8xy - 8xz + 8yz$

4. Originally Posted by Peacewanters007
(2x-2y-2z)^2
solve above!I mean expand using sonme sort of formula
plz dont joke me 4 such a questone I am a student of low level I mean low class oh junior class
Perhaps you should look at it as
$(2x - 2y - 2z) = ((2x - 2y) - 2z)^2 = (2x - 2y)^2 - 2(2x - 2y)(2z) + (2z)^2$
which you should be able to expand on your own from here.

-Dan

5. or you could use the multinomial theorem

(topsquark's method is perhaps easier, but you'll get a messy expression anyway)